P42/p44-MAPK and PI3K are sufficient for IL-6 family cytokines/gp130 to signal to hypertrophy and survival in cardiomyocytes in the absence of JAK/STAT activation - Fahmi, A; Smart, N; Punn, A; Jabr, R; Marber, M; Heads, R (2013)
The effect of differential signalling by IL-6 and leukaemia inhibitory factor (LIF) which signal by gp130 homodimerisation or LIFRβ/gp130 heterodimerisation on survival and hypertrophy was studied in neonatal rat cardiomyocytes. Both LIF and IL-6 [in the absence of soluble IL-6 receptor (sIL-6Rα)] activated Erk1/2, JNK1/2, p38-MAPK and PI3K signalling peaking at 20min and induced cytoprotection against simulated ischemia-reperfusion injury which was blocked by the MEK1/2 inhibitor PD98059 but not the p38-MAPK inhibitor SB203580. In the absence of sIL-6R, IL-6 did not induce STAT1/3 phosphorylation, whereas IL-6/sIL-6R and LIF induced STAT1 and STAT3 phosphorylation. Furthermore, IL-6/sIL-6R induced phosphorylation of STAT1 Tyr701 and STAT3 Tyr705 were enhanced by SB203580. IL-6 and pheneylephrine (PE), but not LIF, induced cardiomyocyte iNOS expression and nitric oxide (NO) production. IL-6, LIF and PE induced cardiomyocyte hypertrophy, but with phenotypic differences in ANF and SERCA2 expression and myofilament organisation with IL-6 more resembling PE than LIF. Transfection of cardiomyocytes with full length or truncated chimaeric gp130 cytoplasmic domain/Erythropoietin receptor (EpoR) extracellular domain fusion constructs showed that the membrane proximal Box 1 and Box 2 containing region of gp130 was necessary and sufficient for MAPK and PI3K activation; hypertrophy; SERCA2 expression and iNOS/NO induction in the absence of JAK/STAT activation. In conclusion, IL-6 can signal in cardiomyocytes independent of sIL-6R and STAT1/3 and furthermore, that Erk1/2 and PI3K activation by IL-6 are both necessary and sufficient for induced cardioprotection. In addition, p38-MAPK may act as a negative feedback regulator of JAK/STAT activation in cardiomyocytes. © 2012 Elsevier Inc.